Influencia del clima laboral en el compromiso organizacional de la Empresa Grifo Paiján S.R.L. - Ventura Torres, Luz Elizabeth (2014)
The main objective of this research is to know the influence of Employee Satisfaction in Organizational Commitment of “Grifo Paiján SRL” company, where exists this problem: How is the influence of the Working Environment in the Organizational Commitment of employees of the company “Grifo Paiján SRL”?, so the following hypothesis is proposed: “The Labour Climate has directly influence in the Organizational Commitment of company workers Grifo Paiján SRL”. The research methodology used was: Applied , no experimental and descriptive Inductive - Deductive Method , Hypothetical - Deductive Method, Synthesis and Analysis - Method ,the design was A cross-sectional Description, the survey was also used as a technique for research. According to the results, I can say that there is a direct relationship between the work environment and organizational commitment, because if there is a better perception of the work environment will be greater worker commitment to the company. Using the results presented in this research, the company to can prepare contingency plans to encourage employees, motivate them, to feel part of the team and promote a pleasant climate that inciting workers to engage every day with the company.